Examining the Health and Medical Staff Perception in Children Aged 9-11 with the Method of Projective Illustration* - Erçin, Emine; Çetinkaya, Şenay (Jour Med Resh and Health Sci, 2023)
Background: Drawing pictures in childhood is an important communication process for children's self-knowledge and introducing themselves. Children designate health and medical staff with the method of projective illustration. Purpose: It is a phenomenological research aimed to examine the "health and health care providers" perceptions of 9-11 aged children. Materials and Method: The present study was in a phenomenological research, and was conducted between 27.10.2016-10.01.2017. For the research, 32 children who have chronic diseases in the Çukurova University Balcal? Hospital, and 30 healthy children studying in a primary school were randomized and were included in the study. Firstly, a questionnaire was applied to the children and their mothers about their socio-demographic characteristics. Then, the children were asked to draw pictures for 30 minutes by giving them 12-color crayons and drawing paper about what they figured out firstly about health-nurse-doctor. Questions were asked to the children about the pictures they drew. Results: Evaluation of the images were made by criteria generated by utilizing the literature and picture evaluation criteria. It was determined that 28 children (87.5%) in the hospital group and all children (100%) in the school group had positive messages in their pictures. It was determined that 17 children in the hospital group drew weak nature figures and 24 children in the school group drew rich nature figures in their pictures. Conclusion: It was seen that all of the children in two groups had positive feelings after drawing the pictures. The health workers, communication tools, teachers and parents have great responsibilities for the formation of the concepts related to health in children. Children generally have difficulty in telling their feelings. When establishing communication with children, nurses may use the drawing picture method just like all the other healthcare professionals. .